Հանրային անվտանգության քաղաքականության արդիականացման միտումները - Վարուժան Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Due to the global universal multi polar processes, the young branch of safety science is a permanent modernization, predicting all the changes which may impend the new public safety agenda. Anyway let’s state, that in the scope of this new born science branch both theorists and experts of the new world didn’t develop yet a unified approach, due to the development of the multi polar world regional characteristics. This young sphere of science (security studies) is now in the development process, which includes historical characteristics and patterns safety policy modernization.
Keywords: Political Science